DIMENSI TEMA CERPEN “PENGARANG TELAH MATI” KARYA SAPARDI DJOKO DAMONO: PENDEKATAN PRAGMATIK - Erisy Syawiril Ammah; Sudarsri Lestari (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2019)
The process of analysis used in this short story is to reveal the theme carried Sapardi Djoko Damomo in his work entitled “Pengarang Telah Mati” through pragmatic approach. This is because the theme is not within the realm of explicit that can be known directly by the reader, but the theme of short story “Pengarang Telah Mati” are in semantic areas described in each problematic in the story. Authors who have discretion in creating an autonomous world of authorship will be trying to hide something that will be delivering a message from a short story. This will provide the knowledge, experience, entertainment and benefit to the reader. Based on data analysts that have been done with a pragmatic approach, it can be concluded that theme “Pengarang Telah Mati” about accountability. A firmness to someone to be responsible for the actions he has dared to do and not leave him.